Answer:
(x) =
![(2x)/(x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kxe1abjx6spz5g8xscaxzss8teo6qo15fy.png)
Explanation:
let y = f(x)
then y =
![(x)/(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mn6hs863cmvu4puxkq9rawwtit22kr18i7.png)
rearrange making x the subject, cross- multiply
y(x - 2) = x
xy - 2y = x ( subtract x from both sides )
xy - x - 2y = 0 ( add 2y to both sides )
xy - x = 2y ( factor out x from each term on the left side )
x(y - 1) = 2y ( divide both sides by (y - 1)
x =
![(2y)/(y-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/umwfovnei28vv9vtzwrj3hhkgd4bg2ow2z.png)
change y back into terms of x
(x) =
![(2x)/(x-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kxe1abjx6spz5g8xscaxzss8teo6qo15fy.png)